(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The importance of economic and technical feasibility studies include all of the investor, the society, the banks, the project and the government. As it will assist in achieving the optimal use of the available economic incomes on the national level and arranging the projects in priority which participates in achieving the government benefit without wasting the amounts .This is the research goal So, the research covered its theoretical aspect, of SAIs and the economic and technical feasibility studies then the role of the auditors in auditing those studies Then a mechanism was proposed includes a guidebook that provides guidelines for organizing the process of preparing and auditing those studies , And also, a program was proposed for those studies then, applied that program in the Kufa University The search is over a set of conclusions and The most important recommendations .